Weak localization, Aharonov-Bohm oscillations and decoherence in arrays of quantum dots - Golubev, D.S.; Semenov, A.G.; Zaikin, A.D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
Combining scattering matrix theory with non-linear σ-model and Keldysh technique we develop a unifiedtheoretical approach enabling one to non-perturbatively study the effect of electron–electron interactions on weak localization and Aharonov–Bohm oscillations in arbitrary arrays of quantum dots. Our model embracesweakly disordered conductors, strongly disordered conductors and (iii) metallic quantum dots. In all these cases at T → 0 the electron decoherence time is found to saturate to a finite value determined by the universal formulawhich agrees quantitatively with numerous experimental results. Our analysis provides overwhelming evidencein favor of electron–electron interactions as a universal mechanism for zero temperature electron decoherence indisordered conductors.